Broadening Perspectives on Broadening Participation: Professional Learning Tools for More Expansive and Equitable Science Communication - Bevan, Bronwyn; Calabrese Barton, Angela; Garibay, Cecilia (Frontiers in Communication, 2020)
Many professionals in the field of science communication have argued that our work too often tends to be designed for people like ourselves—those already interested in, comfortable with, and engaged with science. Thus, our work, ostensibly intended to broaden who engages with STEM, may in fact be exacerbating rather than reducing disparities with regard to who has access to and makes use of designed (versus everyday) opportunities for science engagement. In this conceptual analysis, we posit that inclusive science communication must be conceptualized as a process of cultural exchange, rather than as a process of translation. Thus the goal is not to speak more simply or more loudly, but rather with more understanding and mutualism. We share the results of an exploratory project that developed a suite of research briefs designed to support science communication professionals in reflecting on key structural barriers that operate to institutionalize science as an non-inclusive domain of activity. We conclude that more dialogic ways of professional learning, among science educators, can reveal biases, gaps between goals and reality, and other underlying practices that must be addressed if we are to advance inclusive forms of science communication.